Increasing Public Knowledge Through Health Education on Radio Through Talkshows With Title “The Role of Volunteers in Helping Communities Affected in Disaster” in Program 1 RRI Malang - Sunaryo, Eri Yanuar Akhmad Budi; Evi, Nurul; Rahmatika, Qory Tiffani; Widjayanti, Yhenti; Ramadhan, Muhammad Putra; Masfi, Ahmad; Afiani, Nurma; Kurniawan, Setyo Budi (Inovasi Lokal, 2023)
Volunteers are individuals who voluntarily donate their time and effort to make a positive contribution to others without expecting financial or material rewards. The roles of volunteers before a disaster (pre-disaster) is as supporters in policy formulation, planning, disaster risk reduction, and community disaster prevention and preparedness. This community service (PKM) aims to provide education about the role of volunteers, especially health volunteers, in helping people affected by disasters. The PKM activity was aimed at listeners of the Kiprah Indonesia program, which was broadcasted on Program 1 of the LPP RRI Malang Culture Channel. This PKM activity took the form of a talk show held live at the Kiprah Indonesia event on the Culture Channel Program 1 RRI Malang 105.3 FM, and was also broadcast via live streaming on the official RRI Malang Youtube channel. The community service (PKM) was carried out on December 29, 2022, by broadcasting live on the Kiprah Indonesia event on Program 1 Culture Channel LPP RRI Malang 105.3 FM. The PKM program was a radio talk show. Health education provided by this radio talk show was expected to increase public knowledge about the disaster management cycle, the definition/understanding of volunteers in disaster management, the working principles of volunteers, the five pillars of volunteers in disaster management, the task/duties of volunteer organizations, volunteer management, and also landslide and flood disaster mitigation. This talskhow also aims to provide mitigation and preparedness measures to deal with disasters, especially floods and landslides